Comparison between the quality of life, anxiety and depression of pregnant women who live in rural and urban area in a municipality in the Brazilian Amazon (Research, Society and Development, 2022)
This study aimed to compare pregnant women living in rural and urban areas in a municipality in the Amazon region, in relation to quality of life, levels of common mental disorders, stress and anxiety. A descriptive, exploratory research. A sample of 23 pregnant women attended at a health center in the city of Ouro Preto do Oeste-RO, where interviews were conducted with pregnant women, applying 04 instruments: Sociodemographic, Depression, Anxiety and Stress Scale - Short Form (DASS- 21), World Health Organization Quality of Life (WHOQOL-BREF) and Self-Reporting Questionnaires (SRQ). It was observed that the sociodemographic profile of pregnant women is similar in all variables studied. In relation to the common mental disorder, it was not possible to detect alterations, where all presented normality patterns. In the same sense, when the levels of anxiety, stress and depression were evaluated by DASS21, there were no significant changes. However, the quality of life of pregnant women in urban areas was below that of pregnant women in rural areas, that is, those from urban areas have a worse quality of life in the psychological and social facets. Obtaining information on the pregnant women's profiles is essential to carry out actions to promote their health and also ensure a healthy pregnancy for the pregnant woman and her child.